2015
DOI: 10.1007/s11999-014-3966-2
|View full text |Cite
|
Sign up to set email alerts
|

How Prevalent Are Hazardous Attitudes Among Orthopaedic Surgeons?

Abstract: Background So-called ''hazardous attitudes'' (macho, impulsive, antiauthority, resignation, invulnerable, and confident) were identified by the Federal Aviation Administration and the Canadian Air Transport Administration as contributing to road traffic incidents among college-aged drivers and felt to be useful for the prevention of aviation accidents. The concept of hazardous attitudes may also be useful in understanding adverse events in surgery, but it has not been widely studied. Questions/purposes We surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 12 publications
3
21
0
3
Order By: Relevance
“…The surgeons may overestimate their ability to execute a complex or high‐risk procedure. Bruinsma et al . spoke to 364 orthopedic surgeons and found that 30% of them demonstrated attitudes that represented a potential danger for their patients.…”
Section: Discussionmentioning
confidence: 99%
“…The surgeons may overestimate their ability to execute a complex or high‐risk procedure. Bruinsma et al . spoke to 364 orthopedic surgeons and found that 30% of them demonstrated attitudes that represented a potential danger for their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent research has explored how surgeons also have problems with these psychological constructs: machoism, impulsivity, worry, low resilience or resignation, over-confidence, and resistance to authority (Bruinsma et al, 2015). The authors suggest that certain parenting and coaching styles are contributors to the unhealthy formation of these hazardous attitudes.…”
Section: Development Of the "Hazardous Attitudes" Through Youth Sportsmentioning
confidence: 99%
“…The so-called "hazardous attitudes" (machoism, impulsivity, invulnerability, antiauthority, resignation, and overconfidence) have received an increasing amount of attention for their impact on professional pilots in the United States and Canada, in addition to negative medical outcomes among surgeons who possess them (Bruinsma, Becker, Guitton, Kadzielski, & Ring, 2015). There is other evidence that these attitudes are generally problematic in societies, families, and working environments (Tyrer, Reed, & Crawford, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The author certifies that he, or any member of his immediate family, has no commercial associations (eg, consultancies, stock ownership, equity interest, patent/licensing arrangements, etc) that might pose a conflict of interest in connection with the submitted article. that would be considered dangerously high in pilots [1].…”
mentioning
confidence: 99%
“…A careful reader will identify shortcomings in these articles [1,2]; surgeons are not pilots, and the questionnaires the investigators used have not been validated in surgeons. If you like, consider these articles conversation starters rather than definitive efforts.…”
mentioning
confidence: 99%